NUMERICAL SIMULATION OF FLUTTER CHARACTERISTICS IN TRANSONIC FAN BASED ON HARMONIC BALANCE METHOD - ZHANG Xiang; HUANG XiuQuan; ZHANG HengMing; CHEN YuChun (Jixie qiangdu)
Due to time periodic characteristic of unsteady response induced by blade vibration,using frequency domain harmonic balance computation technique,with structural dynamics analysis,the unsteady flow field around oscillating blades was numerically simulated in one-way fluid-structure coupled manner. The flutter characteristics of blades were predicted by estimating energy transfer between structure and fluid. For the first stage rotor of a transonic fan,the flutter boundary of blades was obtained by analyzing aeroelastic stability of blades with different rotational speeds and back pressure specified. Result shows that,an existence of instability risk under unstalled operation at 100%,95% and 90% rotational speed means a supersonic unstalled flutter for the blades. Comprehensive effect aerodynamic work in the downstream of shock wave and near leading edge of blade tip determines aerodynamic stability of blades under different working points.